2003
DOI: 10.1128/aac.47.12.3795-3798.2003
|View full text |Cite
|
Sign up to set email alerts
|

Artemether Bioavailability after Oral or IntramuscularAdministration in Uncomplicated FalciparumMalaria

Abstract: The antimalarial activity of artemether following oral or intramuscular administration in the plasma of 15 adults with acute uncomplicated Plasmodium falciparum malaria was measured by bioassay. The peak concentrations in plasma following oral administration were higher in patients with acute illness (median, 1,905 mmol of dihydroartemisinin [DHA] equivalents per liter; range, 955 to 3,358 mmol of DHA equivalents per liter) than in patients in the convalescent phase (median, 955 mmol of DHA equivalents per lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 20 publications
0
35
1
Order By: Relevance
“…At the same time, we were concerned that the current standard therapy for severe malaria in PNG, i.m. artemether, could be suboptimal because of poor absorption (12,25,27,32). Evidence that artesunate suppositories are effective for severe malaria in adults (3,21,22) provided further justification for a trial of rectal artesunate with PNG children with complicated P. falciparum infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, we were concerned that the current standard therapy for severe malaria in PNG, i.m. artemether, could be suboptimal because of poor absorption (12,25,27,32). Evidence that artesunate suppositories are effective for severe malaria in adults (3,21,22) provided further justification for a trial of rectal artesunate with PNG children with complicated P. falciparum infections.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, concerns regarding its unpredictable absorption after i.m. injection, particularly with the most severely ill children, exist (12,25,27,32).…”
mentioning
confidence: 99%
“…doses at 0 and 12 h (25). In addition, a variety of studies have suggested a time-dependent reduction in the F values of artemisinin derivatives during treatment (3,14,32,35), including during the first few days of ARTS therapy (24).…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of the relative bioavailabilities of oral versus intramuscular artemether have varied substantially (15,16), in part because there is marked interindividual pharmacokinetic variability with both routes of administration. It is likely, given its poor solubility, that the absolute bioavailability of artemether is much less than that of the chemically related but water-soluble derivative artesunate, which may be as high as 80% (17).…”
mentioning
confidence: 99%